2014
DOI: 10.1108/ejm-10-2012-0598
|View full text |Cite
|
Sign up to set email alerts
|

Multichannel management gets “social”

Abstract: Purpose – This paper aims to investigate customers’ motivations and the decision-making process when choosing a channel in a “social” multichannel environment that includes social media channels, and the complementary and competitive effects compared to traditional channels within the multichannel strategy of a major European telecoms provider. A conceptual framework of multichannel customer behaviour in a “social” multichannel environment is proposed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 39 publications
(69 reference statements)
1
25
0
Order By: Relevance
“…Johannessen et al (2010) point out that in contrary to the analysis of quantitative data, it is important that those who collect the data also analyse and interpret them, which is the case in this study. Theories, hypotheses and understanding are important starting points for the analysis work, which is extremely important as qualitative data must be interpreted (Patton, 2015). The interpretation also depends on the skills of the researchers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Johannessen et al (2010) point out that in contrary to the analysis of quantitative data, it is important that those who collect the data also analyse and interpret them, which is the case in this study. Theories, hypotheses and understanding are important starting points for the analysis work, which is extremely important as qualitative data must be interpreted (Patton, 2015). The interpretation also depends on the skills of the researchers.…”
Section: Discussionmentioning
confidence: 99%
“…The sample was selected in multiple phases. The qualitative nature of the study indicates that generalisability was not relevant as it rather sought to find as much varied information as possible (Mehmetoglu, 2004;Patton, 2015). Firstly, the researchers aimed to include customers' unfavourable experiences with various types of retailers and products, ranging from electronics, cosmetics and food.…”
Section: Data Collection and Methodsmentioning
confidence: 99%
“…It is a social aspect of exchange to share information with others (Ali, 2011;Crocker and Canevello, 2008) and also a major social value for social media users from other community members that use and interact with social media (Obst and Stafurik, 2010). As such, it can be summarised from the above findings that social factors (social interaction, social ties and social support) enhance the use of social media (Dalla Pozza, 2014;Foster et al, 2011;Gironda and Korgaonkar, 2014;Hsiao et al, 2010;Hsu and Wu, 2011).…”
Section: Social Factorsmentioning
confidence: 99%
“…Taking additionally into account that the number of social media users is consistently growing and is expected to exceed 3 billion users by 2021 (eMarketer, 2017), it is not surprising that social media shift to the center of interests of not only entrepreneurs but also researchers. Current empirical evidence related to the impact of social media on economic life concerns mostly: (a) the strengthening of a customer-company relationship and engagement (Mangold & Faulds, 2009;Kaplan & Haenlein, 2010;Bolton, 2011;Tsimonis & Dimitriadis, 2014;Laroche, Habibi, Richard, & Sankaranarayanan, 2012;Lipsman, Mudd, Rich, & Bruich, 2012;Durkin, McGowan, & Murray, 2014), (b) improved efficiency of marketing (Edelman, 2010;Gallaugher & Ransbotham, 2010;Pozza, 2014;Cawsey & Rowley, 2016), or (c) stimulation of brand awareness and loyalty (Silver & Vegholm, 2009;Farshid, Plangger, & Nel, 2011;Laroche, Habibi, & Richard, 2013;Larsson & Vitaoja, 2017). Contributions related to financial aspects of social media adoption are relatively scarce, and concern mostly non-financial companies and links between social media investment and firm value or performance (Plangger, 2012;Paniagua & Sapena, 2014;Kim, Koh, Cha, & Lee 2015a;Kim, Lim, & Brymer, 2015b;Hsu & Lawrance, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Within the first abovementioned literature strand, the authors prove that social media strengthen long-term relationships with clients (Mangold & Faulds, 2009;Kaplan & Haenlein, 2010;Laroche et al, 2012;Lipsman et al, 2012;Durkin et al, 2014), improve efficiency of marketing efforts (Edelman, 2010;Gallaugher & Ransbotham, 2010;Pozza, 2014;Cawsey & Rowley, 2016), generally increase consumer engagement (Bolton, 2011;Tsimonis & Dimitriadis, 2014), and stimulate brand awareness, loyalty, and trust (Silver & Vegholm, 2009;Farshid et al, 2011;Laroche et al, 2013;Larsson & Vitaoja, 2017). As far as the content type of social media activity is concerned, it is shown that the characteristics of Facebook posts such as post type, category, and posting day influence users' interaction in terms of the number of comments and likes, as well as its duration (Cvijikj & Michahelles, 2011).…”
mentioning
confidence: 99%